1988
DOI: 10.1017/s027226310000749x
|View full text |Cite
|
Sign up to set email alerts
|

Origins of Complex Syntax in Interlanguage Development

Abstract: Functionalist analyses of interlanguage (IL) development have been concerned to establish the discoursepragmatic foundations of morphosyntax. A number of domains have been investigated in such work, including referentiality, topiccomment encoding, and temporal reference. The present study extends the focus to the encoding of simple and complex propositions in IL. · Through a longitudinal analysis of conversational data from two Vietnamese learners of American English, the study examines propositional syntax wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
21
0
3

Year Published

1992
1992
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 17 publications
(17 reference statements)
1
21
0
3
Order By: Relevance
“…The most frequent SC type by far was the complementizer dass (‘that’): Each of the 2 participants used it 10 times. This is in line with Sato (), who found that complement clauses were the most frequent type of subordination used by beginning learners. However, the 2 focal learners differed in the range of lexical items and structures governing the complementizer dass .…”
Section: Results Ii: Correlation Between Measuressupporting
confidence: 91%
“…The most frequent SC type by far was the complementizer dass (‘that’): Each of the 2 participants used it 10 times. This is in line with Sato (), who found that complement clauses were the most frequent type of subordination used by beginning learners. However, the 2 focal learners differed in the range of lexical items and structures governing the complementizer dass .…”
Section: Results Ii: Correlation Between Measuressupporting
confidence: 91%
“…Defined as "a main clause plus all subordinate clauses and nonclausal structures attached to or embedded in it" (Hunt, 1970, p. 189), the T-unit was originally used to measure the syntactic complexity of children's written language. Measures of syntactic complexity for spoken discourse range from semantic units (Sato, 1988;Pica et. al., 1989;Kroll 1977) to intonational units (Crystal & Davy, 1975;Chafe, 1980;Crookes & Rulon, 1985;Ellis et al, 1994;Foster & Skehan, 1996) to syntactic units (Quirk et al, 1985;Kroll, 1977;Hunt, 1970).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Bruner, 1978) and has recently attracted serious attention in second language acquisition (SLA) research. Whereas some studies try to describe the emergence of grammar as an overall and continuous development on different grammatical levels (Clahsen, Meisel, & Pienemann, 1983;Klein & Dittmar, 1979), recent longitudinal studies depart from the idea that particular prototypical words and structures have the function of precursors in early learner varieties and are grammaticalized in competition with cognate words and structures that are acquired successively in later stages of the learning process (Dittmar & Kuhberg, 1988;Meisel, 1987;Sato, 1988;Schumacher & Skiba, 1991). These investigations are more detailed in the sense that they describe-according to theoretical approach-selected grammatical variables, communicative functions, or semantic concepts.…”
mentioning
confidence: 99%
“…among other studies Dittmar, 1981;Dittmar & Kuhberg, 1988;Klein, 1982;Meisel, 1987;Sato, 1986;Schumann, 1978). Recently, the emergence of complex syntax and interpropositional relations (complementation, coordination, and modification) has been described within a functional framework by Sato (1988), who adopted the notion of syntactization from Givon's (e.g., Givon, 1979) work on functional grammar. Syntactization is defined by Sato (1986) as "the process through which the targetlike use of morphosyntactic devices in IL [interlanguage] increases over time, while the reliance on discourse pragmatic context declines" (p. 24).…”
mentioning
confidence: 99%
See 1 more Smart Citation